2010
DOI: 10.22146/gamaijb.5511
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Market Activity Announcements: A Study of Price Manipulation on the Indonesian Stock Exchange

Abstract: We investigate stocks involved in the Unusual

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…Nevertheless, ARR recovered at day3 but it wandered around 0% and negative 3%. This result brings the meaning of unusual price movement contain information rather than market manipulation (Hanafi, 2010). Besides, Jiang, Mahoney & Mei (2005) implied that in this case, stock pools carry confirmation such as insider trading rather than pure or noisy price manipulation.…”
Section: Empirical Results and Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, ARR recovered at day3 but it wandered around 0% and negative 3%. This result brings the meaning of unusual price movement contain information rather than market manipulation (Hanafi, 2010). Besides, Jiang, Mahoney & Mei (2005) implied that in this case, stock pools carry confirmation such as insider trading rather than pure or noisy price manipulation.…”
Section: Empirical Results and Discussionmentioning
confidence: 90%
“…Two studies on UMA are worth mentioning. Firstly, Hanafi (2010) investigated price and trading behaviour of stocks involved in the announcement of unusual market activity in Indonesia market. It is found that abnormal returns and trading activities increase on the days leading to positive unusual market activity announcement.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Saham pertama yang dikenai UMA oleh BEI adalah PT Mitra International Resources atau MIRA (Anas dan Nugroho, 2018). Menurut Hanafi (2010), pengumuman UMA berguna bagi investor karena melindungi mereka dari manipulasi harga saham di pasar modal.…”
Section: Kajian Literatur Dan Pengembangan Hipotesisunclassified
“…Menurut Dewi dan Markeling (2017), pengumuman UMA dilakukan agar perdagangan efek tidak terganggu dan tetap teratur sehingga membuat kegiatan menjadi pasti dan tidak berantakan. Menurut Hanafi (2010), sebelum pengumuman UMA diterbitkan oleh BEI, terjadi kenaikan harga, volume, dan frekuensi transaksi pada saham terkait. Ketika dikomparasi, pergerakan harga dan volume transaksi pada saham-saham yang dikenai UMA sama dengan saham-saham yang memberikan abnormal return.…”
Section: Kajian Literatur Dan Pengembangan Hipotesisunclassified